Eighteen-month-olds’ memory interference and distraction in a modified A-not-B task is not associated with their anticipatory looking in a false-belief task - Zmyj, Norbert; Prinz, Wolfgang; Daum, Moritz M. (Frontiers in Psychology, 2015)
Infants’ performance in non-verbal false-belief tasks is often interpreted as if they have understood false beliefs. This view has been questioned by a recent account that explains infants’ performance in non-verbal false-belief tasks as the result of susceptibility to memory interference and distraction. We tested this alternative account by investigating the relationship between infants’ false-belief understanding, susceptibility to memory interference and distraction, and general cognitive development in 18-month-old infants (N = 22). False-belief understanding was tested in an anticipatory looking paradigm of a standard false-belief task. Susceptibility to memory interference and distraction was tested in a modified A-not-B task. Cognitive development was measured via the Mental Scale of the Bayley Scales of Infant Development. We did not find any relationship between infants’ performance in the false-belief task and the A-not-B task, even after controlling for cognitive development. This study shows that there is no ubiquitous relation between susceptibility to memory interference and distraction and performance in a false-belief task in infancy.